Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di Empal Gentong H. Apud Tengah Tani Cirebon - Hajijah, Sitta Nur; Firmani, Andwina; Asyfia, Kholilah Azkiyah (Jurnal EBI, 2022)
Human resources (HR) is a very important factor that cannot even be separated from an organization. In addition, HR is also an influencing factor. So it can be said that a company can develop very rapidly if it has many competent human resources in their fields, on the other hand if the human resources working in a company are not qualified then the development of the company will also be hampered. Factors that can affect employee performance are the work environment and work motivation. The purpose and objective of this study was to determine the effect of work motivation and environment on employee performance at Empal Gentong H.Apud Tengah Tani Cirebon. This research was conducted at Empal Gentong H.Apud Tengah Tani Cirebon. The data collection method used is the sampling method with the research sample totaling 45 people. The analytical method used is multiple regression. The results of the study found that all variables Motivation, Work Environment  had a positive and significant effect on the managerial performance variable. We recommend that Empal Gentong H.Apud Tengah Tani Cirebon further improve all aspects of the company so that managerial performance within the company will be more effective and efficient in carrying out each task and responsibility within the company. Keyword: Motivation, Work Environment, And Employee Performance